Densidade óptica de pigmento macular em uma amostra da população brasileira - Jorge, Letícia Pinto Coelho (2017)
Macula lutea is the region of the retina where the yellow pigments lutein and zeaxanthin are concentrated. Oxidative damage seems to be an important factor for exacerbation of several retinal diseases, such as age-related macular degeneration, and a protective role of macular pigment has been postulated. The quantitative study of macular pigment and its distribution are possible through the determination of macular pigment optical density (MPOD). The objective of this study was to determine the mean MPOD value in a sample of the Brazilian population and to evaluate the influence of sex, age, ethnicity, smoking history and refractive status on MPOD values in this sample. A cross-sectional study was performed. Forty-two healthy patients had both eyes photographed using Visucam 500 (Carl Zeiss Meditec, Jena, Germany) in combination with the MPOD module. Four variables were obtained: maximum MPOD, mean MPOD, MPOD volume and MPOD area. Demographic data and life habits were collected. The mean MPOD value in the studied population was 0.13 density unit ± 0.02. MPOD values were not influenced by gender, smoking history or refraction. MPOD values were significantly higher among black patients when compared to caucasians. There was a positive but low correlation between mean MPOD and age.